2009
DOI: 10.1016/j.cellbi.2009.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Simulated microgravity induce glutathione antioxidant pathwayin Xenopus laevis embryos

Abstract: Space flights cause a number of patho-physiological changes. Oxidative damage has been demonstrated in astronauts after space flights. Oxidative stress is due to an imbalance between production of oxidant and antioxidative defence. In embryos of Xenopus laevis, the glutathione system is an inducible antioxidant defence. For this reason, we investigated the effect of gravity deprivation on endogenous antioxidant enzymes in X. laevis embryos developed for 6 days in a Random Positioning Machine. The results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Moreover these findings correlate with our recent results on antioxidant enzymes induced in X. laevis embryos developed on RPM (Rizzo et al, 2009) suggesting that microgravity exposure might interfere with oxidative stress.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover these findings correlate with our recent results on antioxidant enzymes induced in X. laevis embryos developed on RPM (Rizzo et al, 2009) suggesting that microgravity exposure might interfere with oxidative stress.…”
Section: Resultssupporting
confidence: 91%
“…The RPM exposed X. laevis embryos to a reduced gravity field. As described in detail by Rizzo et al (2009), around 10% of X. laevis embryos developed in simulated microgravity displayed at stage 47 axial malformations. This kind of malformation has been observed in tadpoles (Snetkova et al, 1995; Sebastian et al, 1996), but not when eggs were fertilized under microgravity condition and when a 1‐g condition was simulated during space flight.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Moreover, simulated microgravity and chronic stresses induced antioxidant responses in lymphocytes, brain and muscles [17][20].…”
Section: Resultsmentioning
confidence: 99%
“…Using an agravitropic mutant of Arabidopsis thaliana grown under clinorotation or increased gravity (7 g ), it was shown that HSP70 and glutathione s-transferase 6, among other proteins, are part of a generalized stress response to gravitational changes (Tan et al , 2011). The glutathione antioxidant pathway has also been shown to be induced in Xenopus laevis embryos during simulated microgravity, and was suggested to play a protective role (Rizzo et al , 2009). A further type of stress-related gene present among the microgravity ETSs was polyubiquitin (Table 1, 6 ESTs), where in budding yeast, the stress-inducible polyubiquitin gene, UBI4, has been shown to be upregulated in response to oxidative stress, and has been suggested to play an important role in increasing cellular ubiquitin levels to allow cells to survive under toxic stress conditions (Cheng et al , 1994).…”
Section: Discussionmentioning
confidence: 99%